Is high-speed rail green? Evidence from a quasi-natural experiment in China - Liang Nie; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2021)
Existing studies have investigated the environmental dividends of substituting high-speed rail for other energy-intensive vehicles from an engineering standpoint, but they have yet to explore the economic effects of high-speed rail and the associated carbon emission reduction benefits. To fill the research gap, we use panel data from 285 Chinese cities between 2004 and 2014, and employ a difference-in-difference model to empirically examine the impact of high-speed rail opening on CO2 emissions. Our results show that the opening of high-speed rail reduces local carbon emissions significantly. This finding is robust and is unaffected by outliers, control group selection, time trends, geography and expectation factors, or endogeneity. The mechanism test reveals that the structure, innovation, and FDI effects are three intermediate influence channels. Further research finds that the emission reduction benefit rises as the intensity of high-speed rail opening climbs the ladder, and high-speed rail service has a spillover effect within an 80-kilometer radius. Moreover, the carbon benefit of the Beijing-Shanghai high-speed rail line far surpasses its carbon footprint, indicating that the line is green. Based on these findings, we recommend that China should support the expansion of high-speed rail in order to reduce carbon emissions in a scientific and responsible manner.
Keywords: Q54; Q56; O13; R11; P28; 330; High-speed rail; CO2 emissions; Impact mechanism; Difference-in-difference; China